Analisis Perilaku Pemberdayaan Pegawai; Studi Perilaku Di Sekretariat Kota Bandung - Riyadi Riyadi (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2012)
Empowerment of employees in an organization is one important strategy to encourage the implementation of tasks and organizational function properly. Therefore, every leader in organizations, including government organizations is required to implement the empowerment of employees, because in this case is esserztially empowering employees is one of the competencies that must be possessed by every leader. In general, the ability of a leader in empowering employees, also is a pattern of leadership behaviors that can affect the pattern of work, spirit of work, and employee work motivation, winch is far longer be able to encourage the creation of good organizational performance.